Sana all Noi and Tuy a qualitative study on the same-sex celebrity couple representation of Vice Ganda and Ion Perez on Youtube - Luna, Ana Beatrice Mondragon; Sanchez, Louie Jon A. (Quezon City College of Mass Communication, University of the Philippines, 2023)
This study analyzes the representation of Filipino same-sex couples in the online sphere. particularly the same-sex couple representation of Vice Ganda and Ion Perez in their respective YouTube channels. The research aims to explore the nature of YouTube as a platform for queer creators, to compare the performativity of Vice Ganda and Ion Perez in their vlogs, and to flesh out the implications of their same-sex couple representation to the Filipino queer community at large. In doing so, Butler's theory of gender performativity (1988, 1990) will be used in conjunction with Foucauldian (1978) queer theory and Dyer's Star Theory (1998). The study utilizes Bernard's (2006) textual content analysis to code the research variables, and the data will be analyzed through a thematic analysis. In choosing the unit of analysis, 11 selected videos are picked through purposive sampling by the nature of intersecting events shown in the vlogs of Vice and Ion. This study has demonstrated that Vice and Ion's specific positionality as queer celebrity YouTube personalities enables them to forward and pull back the queer movement through their same-sex couple representation.

Keywords: queer representation, performativity, YouTube, same-sex couple, celebrity
Inaaral ng papel na ito ang representasyon rig Pilipinong artista na same-sex couple sa mundo ng online. Partikular na tatalakayin dito ang representasyon ni Vice Ganda at Ion Perez bilang isang same-sex couple sa YouTube. Layon ng pag-aaral na siyasatin ang YouTube bilang lugar rig paglikha para sa mga miyembro ng queer community, ipagkumpara ang performativity nina Vice Ganda at Ion Perez sa kanilang vlogs, at mahimauy ang mga implikasyon ng kanilang representasyon sa LGBTQIA++ community sa Pilipinas. Sa paggawa nito, gagamitin ang lente ng teorya ni Butler (1988, 1990) tungkol sa gender performativity katuwang ang queer theory ni Foucault (1978) at star theory ni Dyer (1998). Ang pananaliksik na ito ay gumagamit ng textual content analysis ayon sa paraang inilatag ni Bernard (2006) para kumuha ng datos at susuriin ang mga datos gamit ang thematic analysis. Para gawin ito, purposive sampling ang ginamit para mapili ang 11 na bidyong aaralin base sa vlog ng parehong kaganapan sa buhay ni Vice Ganda at Ion Perez. Naipakita sa papel na ito na ang posisyon ni Vice at Ion bilang mga artistang queer sa YouTube ay nagbibigay sa kanila ng kakayahan na i-abante o i-atras ang queer movement sa pamamagitan ng kanilang representayon bilang isanr same-sex couple.

Keywords: queer representation, performativity, YouTube, same-sex couple, celebrity
Vita.
Thesis
Includes bibliographical references (pages 82-94).
Keywords: Performative (Philosophy); Gay couples; Mass media and gay people